2021
DOI: 10.1039/d0ma00860e
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed ITO nanoparticles as hole-selective electrodes for mesoscopic lead-free perovskite solar cells

Abstract: All-solution-processable ITO nanoparticulate electrodes were developed to replace carbon electrodes in mesoscopic hybrid tin-based PSCs to attain a record efficiency of 5.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Song et al showed such an example by replacing a CE with a screen-printed electrode consisting of indium tin oxide (ITO) nanoparticles. [123] Due to the increased light reflectance of ITO as well as its lower WF, which enhances hole extraction, tin-based PSCs' PCE can be increased from 5.4% when the ITO nanoparticle electrode is used in comparison with 3.0% with a CE.…”
Section: Htm-free Pscsmentioning
confidence: 99%
“…Song et al showed such an example by replacing a CE with a screen-printed electrode consisting of indium tin oxide (ITO) nanoparticles. [123] Due to the increased light reflectance of ITO as well as its lower WF, which enhances hole extraction, tin-based PSCs' PCE can be increased from 5.4% when the ITO nanoparticle electrode is used in comparison with 3.0% with a CE.…”
Section: Htm-free Pscsmentioning
confidence: 99%
“…The full sets of Nyquist plots are shown in Figure S11; they were fitted using a suitable equivalent- circuit model. Two semicircles in a Nyquist plot are typically observed from a mesoporous tin PSC; the first and second semicircles are correlated to charge transfer and charge recombination at the perovskite interface, respectively. , The first semicircle was absent in the SAM-based tin PSC, presumably because of rapid charge transfer; it can be associated with high-performance tin PSCs. , We therefore correlated the dominant semicircle shown in Figure S11 with charge recombination. After analysis of these Nyquist plots, the charge recombination resistance is shown as a function of bias voltage in Figure d.…”
mentioning
confidence: 98%
“…40 For the characteristic plots of current density versus voltage shown in Figure S2a, PEDOT:PSS suffers from loss in charge transport to an appreciable extent in comparison with the SAM. Furthermore, light harvesting in a long wavelength region (650−900 nm) can be significantly depressed in tin PSCs; 41 light absorption loss by the HTM hence requires improvement. According to the transmittance spectra shown in Figure S2b, the SAMs dissipate only slightly the near-infrared light transmittance, whereas PEDOT:PSS decreases transmittance by 1−6% over the wavelength region 700−1200 nm.…”
mentioning
confidence: 99%
See 2 more Smart Citations